2023
DOI: 10.3390/agronomy13122932
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Metal-Based Nanopriming for Improving Seed Germination and Initial Growth of Field Pea (Pisum sativum L.)

Gordana Tamindžić,
Sergei Azizbekian,
Dragana Miljaković
et al.

Abstract: Nanopriming is a newly developed seed technology that improves seed germination, initial plant growth, and crop yield by enabling plants to withstand a variety of abiotic stresses. The objective of this study was to evaluate the effectiveness of comprehensive metal-based (Co, Mn, Cu, Fe, Zn, Mo, and Se) nanopriming as compared to hydro- and non-primed seeds of three different pea cultivars in a germination test. Seed priming with nanoparticles (NPs) improved field pea quality via significant increase in germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The nanoparticles of microelements are synthesized in a cover of biogenic polymers, which are gradually absorbed by enzymes in plant cells with a dosed release of atoms of elements, leading to prolonged action and the absence of inhibition of plant development. It has been established that the bio-polymer-stabilized colloidal solutions of nanoparticles of microelements (Co, Mn, Cu, Fe, Zn, Cr, Se, Mo, and Ag) in various combinations and concentrations are low-toxic, non-eco-, and phytotoxic, and do not cause long-term consequences [ 98 , 99 , 100 ]. To the best of our knowledge, the phytotoxicity of these nanoprimings on pea grains and soil has not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles of microelements are synthesized in a cover of biogenic polymers, which are gradually absorbed by enzymes in plant cells with a dosed release of atoms of elements, leading to prolonged action and the absence of inhibition of plant development. It has been established that the bio-polymer-stabilized colloidal solutions of nanoparticles of microelements (Co, Mn, Cu, Fe, Zn, Cr, Se, Mo, and Ag) in various combinations and concentrations are low-toxic, non-eco-, and phytotoxic, and do not cause long-term consequences [ 98 , 99 , 100 ]. To the best of our knowledge, the phytotoxicity of these nanoprimings on pea grains and soil has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional transmission electron microscopy method for measuring the size of nanoparticles implies a dry sample, while the water removal from volumetric nanoparticles leads to incorrect results that differ from the actual sizes of nanoparticles in the initial structure of aqueous colloids [ 101 ]. Therefore, dynamic scattering spectroscopy was used to measure the size of nanoparticles in the colloids [ 100 , 102 ] in two accredited laboratories: The Centre for Research and Testing of Materials of the Institute of Powder Metallurgy (Minsk, Belarus) and the Fraunhofer Institute for Ceramic Technologies and Systems IKTS (Dresden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the nanomaterials used for seed priming are mineral elements, such as cobalt (Co), zinc (Zn) and iron (Fe). It has been shown that metal-based nanomaterials (Co, Mn, Cu, Fe, Zn, Mo, and Se) can significantly improve pea seed germination performance and, thus, its field quality performance [109]. While nano-priming can significantly improve seed germination and seedling performances, particularly when under stress, it may also have some negative effects, such as the phytotoxicity.…”
Section: Nano-primingmentioning
confidence: 99%
“…The usage of nanoparticles (NPs) as priming agents (nano-priming) could harness the advantages of NPs like rapid internalization and complex biological effects involving physiological and metabolism modifications [5]. Metal (Fe, Ag, Zn, Mn, Cu), selenium, and metal oxide (ZnO, Fe 3 O 4 ) NPs were proven to be efficient priming agents [5,9,10]. Some NPs facilitate electron exchange and enhance surface reaction capabilities with various components present in plant cells and tissues [11]; others can influence the expression of genes that are drought-inducible [12].…”
Section: Introductionmentioning
confidence: 99%